(untitled) (Physical Education, Health and Social Sciences, 2026)
Soil salinity is a major abiotic constraint limiting potato (Solanum tuberosum L.) productivity and tuber quality, particularly in arid and semi-arid regions. Salinity induces osmotic stress, ionic toxicity, and oxidative damage, resulting in reduced photosynthesis, impaired nutrient uptake, and significant yield losses. The present study synthesizes current advances on the integrated use of zinc oxide nanoparticles (ZnO NPs) and organic manures as a sustainable strategy to mitigate salinity stress in potato cultivation. ZnO nanoparticles enhance plant tolerance by improving zinc bioavailability, sustaining photosynthetic efficiency, activating antioxidant defense systems, and regulating stress-responsive hormonal and molecular pathways. In parallel, organic manures improve soil physical structure, increase cation exchange capacity, reduce sodium toxicity, and stimulate beneficial soil microbial communities. The synergistic application of ZnO NPs and organic amendments significantly improves plant growth, tuber yield components, starch accumulation, antioxidant profiles, and zinc biofortification under saline conditions. Moreover, this integrated nano-organic approach contributes to soil health restoration while minimizing environmental risks associated with excessive chemical fertilizer use. Overall, the combined use of ZnO nanoparticles and organic manures represents a promising, eco-friendly strategy for enhancing potato productivity, tuber quality, and nutritional value in salt-affected soils, offering practical implications for climate-resilient and sustainable agriculture.